Mongolia : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
This is the first Country Procurement Assessment Report (CPAR) prepared by the WB for Mongolia since it commenced assisting the country's development program in 1993. Starting in 1998 Mongolia has achieved a great deal in developing a fair and transparent public procurement system, and even during the timeframe of this CPAR preparation, further positive steps have been taken. With a few more relatively straightforward refinements over the next few years, the system can mature further to serve Mongolia's rapid transition to a market economy. The main objective of this CPAR is to review the efficiency of procurement processes in Mongolia in all sectors and, in close cooperation with the Government, to develop an action plan to address areas found to need strengthening in order to improve efficiency and transparency of procurement that would in turn promote higher rates of economic growth. Included in the scope of the work is an analysis of the current public and private sector procurement framework and practice, including the law; an assessment of risks in current procurement practices and recommendations for alleviating these risks; and an identification of areas where beneficial improvements to framework and practice may be made and development of an action plan for implementing these improvements.